Application of Potassium Fertilizer and Chicken Coop Fertilizer Against Growth and Production of Shallots (Allium ascalanicum L.) - Andy Pradana; Al Machfudz WDP (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the application of potassium fertilizer and chicken manure to the growth and production of shallots (Allium ascalanicum L.). The study used a randomized block design with 2 factors repeated 3 times. Factor 1: Potassium Fertilizer 40,60,80 kg/ha. Factor 2: Chicken Manure 5,10,15 tons/ha. The results showed that the application of potassium fertilizer and chicken manure did not interact with either the growth phase or the production phase of the plant on all observation variables, while the potassium fertilizer treatment showed significantly different results only on the plant vegetative growth parameters, namely the number of leaves at the age of 7 days after planting, namely ( 8,111 strands), while the vegetative phase had no significant effect on the number of tubers per clump, wet weight of tubers per clump, wet weight of tubers per plot, dry weight of sun-dried tubers per clump, and dry weight of sun-dried tubers per plot. While the treatment of chicken manure had a significant effect on the vegetative growth phase of plants, namely the length of plants at 28 DAP (30.278 cm) and 35 DAP (32.704 cm), on the number of leaves at 7 DAP (8,000 strands). While the generative phase (60 DAP) significantly affected the number of tubers per clump, namely (5,889 grams), wet weight of tubers per clump (38,333 grams), wet weight of tubers per plot (319,000 grams), dry weight of sun-dried tubers per clump. namely (23.074 grams), and the dry weight of sun-dried tubers per plot (191.889 grams).